RELATIONSHIP OF FAMILY MOTIVATION AND THE HEALTH OFFICERS' ROLES WITH MOTHER'S BEHAVIOR IN GIVING VITAMIN A TO TODDLER (CASE STUDY IN THE TEGAL ARUM HEALTH CENTER TEBO DISTRICT, JAMBI PROVINCE) - Sari, Puspita; Sayuti, Solihin; Rozalia (Journal of Public Health Research and Community Health Development, 2022)
ABSTRACT Background: Vitamin A is an indispensable nutrient for humans and very important in physiological processes of the body, including cell growth, improving visual function, improving immunology and body growth. Giving high dose of vitamin A for infants, toddlers and postpartum mothers could decrease morbidity and mortality of infants and toddlers. The percentage of Tegal Arum Public Health Center in giving Vitamin A to toddlers was low (37,30%) while the target indicator was 100%.Objective: This study aims to determine the description and relationship of family motivation and the role of officers with maternal behavior in vitamin A in toddlers in the Tegal Arum public Health Center, Tebo Regency, Jambi Province.. Methods: This research was a quantitative study with a cross-sectional design, using proportional random sampling. In this study, the samples were mothers who had toddlers in the working area of "‹"‹the Tegal Arum Public Health Center, Tebo Regency, with the number of samples in this study amounting to 82 people. Results: A total of 47 (57,3%) respondents had poor maternal behavior in giving vitamin A to toddlers, 45 (54,9%) respondents had low motivation, 59 (72,0%) respondents had poor family support, 54 (65,9%) of respondents have a less good role of officers. There is a relationship between motivation (p-vaue:0.001) family support (p-value:0.001) the role of officers (p-value:0.002) with mother's behavior in giving Vitamin A in toddlers in the Tegal Arum Public Health Center, Tebo Regency, Jambi Province Conclusion: As input for Public Health Center, there is a need for outreach to health workers, especially village Integrated Health care Center cadres regarding the provision of vitamin A by providing information and counseling to mothers to administer vitamin A ABSTRAK Latar Belakang: Vitamin A merupakan zat gizi yang sangat diperlukan bagi manusia, karena zat gizi ini sangat penting agar proses-proses fisiologis dalam tubuh berlangsung secara normal, termasuk pertumbuhan sel, meningkatkan fungsi penglihatan, meningkatkan imunologis dan pertumbuhan badan Pemberian vitamin A dosis tinggi pada bayi, balita dan ibu nifas dapat menurunkan angka kesakitan dan kematian bayi dan balita. Puskesmas Tegal Arum pemberian Vitamin A pada anak balita tergolong rendah dengan persentase 37,30% sedangkan target indikator gizi sebesar 100%.Tujuan: Penelitian ini adalah untuk mengetahui gambaran dan hubungan motivasi keluarga dan peran petugas dengan perilaku ibu dalam vitamin A pada balita di Wilayah Kerja Puskesmas Tegal Arum Kabupaten Tebo Provinsi Jambi. Metode: Penelitian ini merupakan penelitian kuantitatif dengan Desain penelitian ini adalah Cross Sectional menggunakan Proposional Random Sampling Pada penelitian ini yang menjadi sampel adalah ibu yang mempunyai balita di wilayah kerja puskesmas Tegal Arum Kabupaten Tebo,dengan jumlah sampel dalam penelitian ini berjumlah 82 orang. Hasil : Sebanyak 47 (57,3 %) responden memiliki perilaku Ibu dalam pemberian vitamin A pada balita Kurang Baik, 45 (54,9 %) responden memiliki motivasi rendah, 59 (72,0%) responden memiliki dukungan keluarga kurang baik, 54 (65,9 %)  responden memiliki peran petugas kurang baik.Ada hubungan antara motivasi (p-vaue:0,001) dukungan keluarga (p-value :0,001) peran petugas (p-value:0,002) dengan perilaku ibu dalam pemberian Vitamin A pada balita di Wilayah Kerja Puskesmas Tegal Arum Kabupaten Tebo Provinsi Jambi. Kesimpulan: Sebagai masukan bagi Puskesmas perlu adanya sosialisasi terhadap petugas kesehatan khususnya kader posyandu desa mengenai pemberian vitamin A dengan cara memberikan informasi dan konseling kepada ibu untuk melakukan pemberian vitamin A